Application of fuzzy logic based control algorithms on a railway vehicle considering random track irregularities - Sezer, Semih; Atalay, Ali Erdem (SAGE PUBLICATIONS LTD, 2012)
The vibrations of a railway vehicle are usually caused by track irregularities. These vibrations have to be suppressed for ride comfort and safe transportation. In this study, the comprehensive full railway vehicle model, consisting of 54 degrees-of-freedom, displacements and accelerations are investigated firstly, for random track irregularities. Additionally, using the developed model, the car body vibrations, caused by a lateral and two vertical random track irregularities, are controlled by active controllers, placed between the car body and bogies. The fuzzy logic based algorithms herein are used for realizing the active control of car body vibrations. The simulations of vibration analysis are obtained in time and frequency domains and compared with passive controlled status. The robustness of the designed controllers is verified by simulations, carried out for the cases of the car body mass variations. The results show the effectiveness of the proposed algorithms, especially for the self-tuning fuzzy logic control algorithm.
Keywords: Active control of vehicle vibrations; dynamic modeling; railway vehicle dynamics; simulation of vibrations; NEURAL-NETWORK CONTROL; VIBRATIONS; SIMULATION; DYNAMICS; SYSTEM; MODEL; Acoustics; Engineering; Mechanics